De novo transcriptome characterization of Ulva lacinulata under in situ emersion/immersion cyclic conditions. - López Parages, María; Sánchez de Pedro Crespo, Raquel; Smerdou-Gámez, Carlos (My University, 2023)
The green algal genus Ulva Linnaeus (Ulvaceae, Ulvales, Chlorophyta) displays a worldwide distribution in marine, freshwater and brackish ecosystems, and are really well adapted to fluctuating natural environments. Despite increasing interest on the analysis of the ecophysiological responses showed by organisms to face environmental shifts, knowledge of the genetic and molecular mechanisms underlying those responses are still scarce. These responses determine the survival of organisms under pressure of different environmental stresses and the regular ecosystem behaviour. In order to disentangle the genetic networks that might regulate the adaptation mechanisms of these organisms in a changing environment, the characterization of the de novo transcriptome from Ulva lacinulata derived from a coastal ecosystems of southern Spain under in situ cyclic conditions of emersion/immersion by using Next Generation Sequencing technologies was carried out. Transcriptome sequencing and transcript-level expression analysis were performed by Illumina®NextSeq® 550 system platform. A total of 100,251 unigenes were expressed during emersion/immersion process. Based on the differentially expressed genes (DEGs), genes associated with different biosynthetic metabolic pathways were annotated according to Gene Ontology and Kyoto Encyclopedia of Genes and Genomes Orthology (KEGG). These findings shed light on the molecular mechanisms underlying rapid and successful ecophysiological response of marine macroalgae in cyclic tidal conditions.
Keywords: Algas marinas - Fisiología; Algas marinas - Genética; Transcriptomic; Cyclic conditions; Next Generation Sequencing Technologies; Differentially expressed genes; Ulva lacinulata; Emersion/Immersion